1958
DOI: 10.1021/j150559a007
|View full text |Cite
|
Sign up to set email alerts
|

The Radiation Chemistry of Isopropyl Acetate and Isopropenyl Acetate

Abstract: T.b.e .pro&lcts formed. in .. the irradiation of .liquid 1soprop~1 acetate end isopropenyl acetate 'With helium ions have been studied at ro001•temperature end. : • at f!JJ°C,. llb.e reduced ~eta are :tonned in lmrer yieUJ, fn: •, isopropenyl. al!etate:• •• than in .. isopropyl aeeta.te. by a factor •of about three~. l\. factor-Of-thirty higher "polymer'' yield tram isopropenyl Meta.te indicates that 'radicals, ~c;h 1n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1959
1959
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous investigations of the mass spectra of esters have been limited primarily to methyl (1,18) and aromatic esters (12). Newton and Strom have compared the spectra of isopropyl and isopropenyl acetate (22). Several investigations of the formation of rearrangement ions in mass spectra have been reported (1, 6, 9,10,15,17, 21, 27).…”
mentioning
confidence: 99%
“…Previous investigations of the mass spectra of esters have been limited primarily to methyl (1,18) and aromatic esters (12). Newton and Strom have compared the spectra of isopropyl and isopropenyl acetate (22). Several investigations of the formation of rearrangement ions in mass spectra have been reported (1, 6, 9,10,15,17, 21, 27).…”
mentioning
confidence: 99%
“…[118] Poly-isopropanol (PiPOH) was then obtained by hydrolysis of the acetyl moieties (Scheme 34, a). The effects of helium ions irradiation towards liquid iPAc and isopropyl acetate have been studied at room temperature and at 80 °C by Newton et al [119] It was found a factor of thirty higher "polymer" yield when iPAc was used in place of isopropyl acetate, indicating that the polymerization occurs through the double bond. [119] iPAc was also investigated for various copolymerization processes.…”
Section: Reactions Of the C=c Double Bondmentioning
confidence: 99%
“…The effects of helium ions irradiation towards liquid iPAc and isopropyl acetate have been studied at room temperature and at 80 °C by Newton et al [119] It was found a factor of thirty higher "polymer" yield when iPAc was used in place of isopropyl acetate, indicating that the polymerization occurs through the double bond. [119] iPAc was also investigated for various copolymerization processes. Vinyl chloride and iPAc were emulsion copolymerized in sealed tubes at 45°C.…”
Section: Reactions Of the C=c Double Bondmentioning
confidence: 99%